Beware of the crocodile - Jenkins, Martin, 1959- (Candlewick Press, 2019)
"All is quiet on the water. Then, in a flash, there's a sudden lunge and a tremendous splash. And then? Oh dear. There's a lot of twirling and thrashing: a hungry crocodile has found something to eat. But crocodiles also love to nap on warm sandbanks and cool off in calm waters. And they're very gentle with their babies. There's a lot to learn about crocodiles in this captivating look at one of the world's deadliest and toothiest animals. Beware!"--Dust jacket front flap.